Japan : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2017)
This paper assesses the stability of the financial system in Japan. Although the financial system has remained stable, the low profitability environment is creating new risks, and pressures are likely to persist. The search for yield among banks has led some to expand their overseas activities, and more generally to a growth in real estate lending and foreign securities investments. Efforts to increase risk-based lending to small-and medium-sized enterprises are welcome, but many banks still need to develop commensurate credit assessment capacities. Stress tests suggest that the banking sector remains broadly sound, although market risks are increasing, and there are some vulnerabilities among regional banks.